Evaluating the impact of gabapentinoids on sleep health in patients with chronic neuropathic pain: a systematic review and meta-analysis. Issue 3 (March 2020) - Kapustin, Daniel; Bhatia, Anuj; McParland, Aidan; Trivedi, Aditya; Davidson, Alexandra; Brull, Richard; Singh, Mandeep
Abstract : Abstract: Chronic neuropathic pain (NP) is debilitating and impacts sleep health and quality of life. Treatment with gabapentinoids (GBs) has been shown to reduce pain, but its effects on sleep health have not been systematically evaluated. The objective of this systematic review and meta-analysis was to assess the relationship between GB therapy dose and duration on sleep quality, daytime somnolence, and intensity of pain in patients with NP. Subgroup comparisons were planned for high- vs low-dose GBs, where 300 mg per day or more of pregabalin was used to classify high-dose therapy. Trial data were segregated by duration less than 6 weeks and 6 weeks or greater. Twenty randomized controlled trials were included. Primary outcome measures included pain-related sleep interference and incidence of daytime somnolence. Secondary outcomes included daily pain scores (numerical rating scale 0-10) and patient global impression of change. Significant improvement in sleep quality was observed after 6 weeks of GB treatment when compared with placebo (standardized mean difference 0.39, 95% confidence interval 0.32-0.46 P < 0.001). Increased daytime somnolence was observed among all GB-treated groups when compared with placebo. Treated patients were also more likely to report improvement of patient global impression of change scores. Pain scores decreased significantly in patients both after 6 weeks of treatment ( P < 0.001) and in trials less than 6 weeks ( P = 0.017) when compared with placebo. Our data demonstrate that GBs have a positive impact on sleep health, quality of life, and pain in patients with NP syndromes. However, these benefits come at the expense of daytime somnolence. Abstract : Supplemental Digital Content is Available in the Text.